Comparison between low cost USB nailfold capillaroscopy and videocapillaroscopy: a pilot study. (24th November 2020) - Berks, Michael; Dinsdale, Graham; Marjanovic, Elizabeth; Murray, Andrea; Taylor, Chris; Herrick, Ariane L
Abstract: Objectives: Universal serial bus (USB) microscopy (capillaroscopy) could provide all rheumatologists with an easy-to-use, low-cost tool to examine the nailfold capillaries to facilitate early diagnosis of SSc. The objectives of this pilot study were to examine the feasibility of acquiring and analysing images using USB microscopy and to compare results to videocapillaroscopy. Methods: Videocapillaroscopy and USB microscope images were obtained from the right and left ring fingers of 20 patients with SSc and 20 healthy control subjects. In addition to generating panoramic capillary mosaics from across the whole nailbed, custom software made fully automated measurements of vessel structure including capillary width and density. The area under the receiver operating characteristic curve (AZ ) was used to measure separation between the SSc and healthy control groups. Results: High quality images could be generated from the USB microscope, with reconstructed USB images comparing very favourably with those obtained using videocapillaroscopy. Using USB microscope images, the receiver operating characteristic curve AZ for group separation based on mean width was 0.81 (standard error 0.120) compared with 0.81 (standard error 0.095) for the (gold standard) videocapillaroscopy. The receiver operating characteristic curve AZ for group separation using capillary density was 0.48 (standard error 0.16) for USB microscope images, compared with 0.70 (standard error 0.10) for videocapillaroscopy. Conclusion: In this pilot study, USB capillaroscopy was able to discriminate between patients with SSc and controls as well as videocapillaroscopy on the basis of capillary width. This finding, together with the high-quality images obtained, highlights the potential of USB capillaroscopy as a low-cost, easily accessible clinical and research tool.